DEM modelling of retained backfill: Influence of particle shape for different stress paths and densities - Altunbaş, Adlen; Soltanbeigi, Behzad; Çinicioğlu, Özer (Techno Press, 2021)
This paper investigates the relative influences of backfill particle properties and imposed stress path on the response of retained granular assemblies. The characteristics considered are particle shape, backfill density, and gradation. For this purpose, Discrete Element Modelling (DEM) is employed to simulate the development of passive and active states in a cohesionless soil. Particle shape is assessed first through restraining the rotational freedoms of spherical particles (i.e. assigning rolling resistance), and the next by joining spherical particles (i.e. multisphere). The obtained results show that it is not possible to capture realistic response using a contact-independent rolling resistance model. Then, using backfill models composed of particles with various angularities, which are prepared at two alternative densities, backfill deformation towards passive and active states are simulated. Results are used to judge the relative weights of the influences of particle angularity, backfill density and gradation on back behaviour, employing both qualitative and quantitative methods. For densely packed clump particles varying particle angularity influences backfill density, shear band characteristics, geometries of the resulting failure wedges, and distribution of lateral backfill pressure. In addition, the effect of shape complexity is evaluated for packings with identical initial density, which are relatively loose. Overall, comparing the results from packings with different densities revealed the idea that particle shape effect is density and stress-path dependent.
Keywords: Active State; Density; Discrete Element Modelling (DEM); Particle Shape; Passive State; Retaining Wall